2021
DOI: 10.37934/jrnn.3.1.4652
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Chitosan Nanoparticles CrossLinked with Tripolyphosphate

Abstract: Chitosan nanoparticles (ChNPs) have been extensively examined for various biomedical applications due to their advantages include large surface area, biodegradability, and biocompatibility. The purpose of this research was to synthesize ChNPs using a simple ionic gelation technique by the interaction of low molecular weight chitosan (LMWC) and sodium tripolyphosphate (TPP) as a cross-linking agent. ChNPs, TPP, and LMWC were analysed by X-ray diffraction (XRD) and Fourier transforms infrared (FTIR) spectra that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…X-ray diffraction studies of native chitosan exhibit very broad peaks at 2θ = 10.82° and 2θ = 20.19° that correspond to the plane of (020) and (110), respectively [16]. After crosslinking with TPP during the fabrication of chitosan NPs, the crystalline structure of native chitosan was destroyed, where the peak intensity of (020) and (110) was observed to disappear and shifting of small peak near to 2θ = 18.89° in the pattern of cross-linked Cs-NPs respectively, this is consistent with earlier findings and reveals the amorphous nature [17][18][19]. The decrease in crystallinity could be related to the fact that chitosan NPs are formed of a dense network structure of interpenetrating counter ions of TPP, which crosslink the chains of polymer.…”
Section: X-ray Diffraction Analysis Of Cross-linked Cs-npssupporting
confidence: 87%
See 1 more Smart Citation
“…X-ray diffraction studies of native chitosan exhibit very broad peaks at 2θ = 10.82° and 2θ = 20.19° that correspond to the plane of (020) and (110), respectively [16]. After crosslinking with TPP during the fabrication of chitosan NPs, the crystalline structure of native chitosan was destroyed, where the peak intensity of (020) and (110) was observed to disappear and shifting of small peak near to 2θ = 18.89° in the pattern of cross-linked Cs-NPs respectively, this is consistent with earlier findings and reveals the amorphous nature [17][18][19]. The decrease in crystallinity could be related to the fact that chitosan NPs are formed of a dense network structure of interpenetrating counter ions of TPP, which crosslink the chains of polymer.…”
Section: X-ray Diffraction Analysis Of Cross-linked Cs-npssupporting
confidence: 87%
“…This process involves cationic chitosan reacting spontaneously with an anionic cross-linking agent, often tripolyphosphate (TPP), to create a polyelectrolyte complex known as TPP/Chitosan. This method relies on the electrostatic interaction of positively charged chitosan amino groups with negatively charged sodium tripolyphosphate (TPP) groups acting as a cross-linking agent [12]. In order to produce the material, TPP solution must be added to chitosan while it is being continuously stirred magnetically at room temperature [3].…”
Section: Introductionmentioning
confidence: 99%
“…The significant peak indicates the crystalline nature of chitosan films, and per the literature, these peaks correspond to the (110) plane [JCPDS card no. 04-0784] . As no shift in the 2θ values of the peaks for glycerol-added films was observed, we conclude that the glycerol has not altered the crystal structure of chitosan.…”
Section: Resultsmentioning
confidence: 66%
“…04-0784]. 52 As no shift in the 2θ values of the peaks for glycerol-added films was observed, we conclude that the glycerol has not altered the crystal structure of chitosan. Okuyama et al 37 reported two peaks one at 2θ = 10°and the other at 20°for chitosan.…”
Section: ■ Materials and Methodsmentioning
confidence: 67%
“…Ionic gelation between chitosan and TPP created crosslinks that physically entrapped the drug, with Tween 80 enhancing the particle surface. Concentration optimization revealed a 0.7 mg/mL TPP concentration yielding nanoparticles within the desired 50-150 nm size range [13]. Maintaining a pH of 5 prevented agglomeration.…”
Section: Size Optimizationmentioning
confidence: 99%